2018
DOI: 10.1097/md.0000000000010993
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and care burden in primary caregivers of liver transplantation recipients in China

Abstract: So far, liver transplantation (LT) has become the most effective way to treat end-stage liver-related diseases. As we all know, a stable caregiver is crucial to LT recovery. However, compared with LT patients, few studies were focused on LT caregivers.This study aimed to describe the quality of life (QoL), care burden, and their related factors in caregivers of LT patients in Shanghai, China.We collected 225 liver transplanted patients and their corresponding caregivers’ social demographic and medical informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 27 publications
1
14
0
4
Order By: Relevance
“…In the present study, approximately half the participants were working when they committed to being a caregiver. Similar to others reports, 5,17,18 caregivers who were working had to suspend their own careers to take up a caregiving role, which may have contributed to additional stress. None of the caregivers in the present study had insurance coverage for caregiver-related expenses, and in some situations, this also contributed to financial concerns.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In the present study, approximately half the participants were working when they committed to being a caregiver. Similar to others reports, 5,17,18 caregivers who were working had to suspend their own careers to take up a caregiving role, which may have contributed to additional stress. None of the caregivers in the present study had insurance coverage for caregiver-related expenses, and in some situations, this also contributed to financial concerns.…”
Section: Discussionsupporting
confidence: 76%
“…This finding is notable since transplant caregiver knowledge has been associated with less anxiety and depression, and confidence in handling daily tasks, and improved quality of life. 5,12 Moreover, caregiver quality of life has been shown to impact transplant recipients’ mortality, with greater impairments in caregiver health perceptions at 1 year predicting poorer transplant recipient survival. 6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that a poor caregiver QOL predicts that a LT recipient will receive low quality care by their caregiver. 1,2,6 Furthermore, caregivers with a heavy financial burden have a poorer QOL, which leads to less optimal care delivery for the LT recipient. 1,2 The focus during the LT evaluation process is often shifted to the individual receiving the transplant.…”
Section: Introductionmentioning
confidence: 99%
“…Entre los requerimientos para someterse a un trasplante, el contar con un Cuidador Primario Informal (CPI) que acompañe al paciente es vital. El cuidador cumple con múltiples funciones que incluyen: contribuir al equilibrio y estabilidad emocional del paciente; favorecer la adherencia al tratamiento; auxiliar en las medidas de higiene, nutrición, ocio, así como descanso; realizar trámites hospitalarios; proveer y ministrar medicamentos; asistencia en actividades relacionadas con la rehabilitación con el fortalecer la adaptación a la cotidianidad 6,[12][13][14][15][16][17] . Todas estas acciones son parte de los objetivos que se relacionan con el índice elevado de supervivencia junto con la calidad de vida, durante y después del trasplante 18,19 .…”
Section: Introductionunclassified